An Econometric Study of the Development of Invested Agricultural Lands in Lattakia Governorate During the Period 2000-2020 - درويش, دلامة; غسان يعقوب , (Latakia University Journal -Biological Sciences Series, 2023)
The research aimed to study the changes that occurred in the agricultural holdings in Lattakia Governorate during the period 2000-2010, and to know their direction and growth. The research relied on the statistical data and data available in books, references, periodicals, reports, and agricultural statistical collections, with the aim of diagnosing the reality of invested agricultural holdings in Lattakia Governorate, and the time frame for the study was determined during the period 2000-2020. Eviews statistical software was relied upon. 10 In analyzing the data, the standard quantitative approach was used, where the unit root and stability test was used, and ARIMA models to predict the invested agricultural holdings for future periods. The results showed that the area of invested agricultural holdings-maintained stability after 2011, and took a random trend between increase and decrease during the period 2002-2010. -2024, which indicates no improvement in the economic reality during these years.